Persepsi Ulama Palembang Terhadap Pondok Pesantren Al Zaitun Indramayu - M.Rafly Pratama; Candra Darmawan (Social Science and Contemporary Issues Journal, 2023)
This thesis is entitled "Perceptions of Palembang Ulama towards the Al Zaitun Indramayu Islamic Boarding School". This research method uses a qualitative method with a case study research method. The data sources used are primary data and secondary data. Data collection techniques include observation, interviews and documentation. Data analysis techniques consist of data reduction, data presentation, and drawing conclusions. The results of this research show that the perception of one of the famous Kyai, namely KH. Solihin Hasibuan in Palembang, as well as religious figures and community leaders regarding several evidences of heresy at Al zaitun, all agree that the teachings at the Al zaitun Islamic boarding school are teachings that deviate from Islamic law and norms, some of the evidence that has been mentioned, such as the prayer rows which are at a distance, the school used in the lodge is the Soekarno school of thought and several things that are implemented in Al zaitun, Friday prayer khotibs are allowed to be women, and female congregation members can pray close to the men's rows. , and the distance between the men's rows is half a meter. Other Islamic boarding schools must be clever in sorting and choosing and deepening the religious knowledge taught by the Prophet Muhammad so that they do not get confused and deviate from the scientific knowledge of the Prophet Muhammad, and it has been described by several media that the leader of the Al zaitun Islamic boarding school is Panji Gumilang after being appointed as suspect in the case of religious defamation and this news is already widely known by the wider community in Indonesia